(untitled) (Marketing Journal, 2025)
This article explores the current state, structural dynamics, and development trends of Uzbekistan’s transport services sector. The study emphasizes the dominance of road transport, the rapid growth of logistics and infrastructure modernization, and the co untry’s strategic efforts to overcome its landlocked geography through active participation in international transport corridors —particularly the Middle (Trans -